From Fear to Sharing: How Digital Marketing Triggers FOMO and Customer Engagment to Drive E-WOM for Nike Shoes In Indonesia - Riza Aqil Wafi; Firdaus Firdaus; Hendar Prihardi; Jumai Jumai (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The rapid growth of digital marketing has intensified psychological responses such as Fear of Missing Out (FOMO) and customer engagement, particularly among consumers who actively interact with brands through digital platforms. This phenomenon is increasingly relevant in Indonesia, where global footwear brands such as Nike extensively utilize digital marketing strategies. Grounded in the Stimulus-Organism-Response (S-O-R) framework, this study examines the influence of digital marketing on FOMO, customer engagement, and electronic word of mouth (e-WOM) among Nike consumers in Indonesia. A quantitative approach was employed through a survey involving 200 respondents who had purchased Nike products and were exposed to Nike digital marketing content. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results reveal that digital marketing has a positive and significant effect on FOMO, customer engagement, and e-WOM. Customer engagement also positively and significantly influences e-WOM and mediates the relationship between digital marketing and e-WOM. In contrast, FOMO does not significantly affect e-WOM and fails to mediate the relationship between digital marketing and e-WOM. These findings indicate that customer engagement plays a more important role than FOMO in encouraging consumers to share experiences and recommendations online. The study extends the application of the S-O-R framework by demonstrating that engagement represents a stronger mechanism than psychological urgency in generating e-WOM behavior for high-involvement products. The findings also provide practical implications for engagement-oriented digital marketing strategies.